Detecting document similarity in large document collecting using MapReduce and the Hadoop framework - Momtaz, Anik; Amreen, Sadika (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2012.